Effects of Tomato Juice Supplementation on the Reproductive Performance, Hematological Indices and Oxidative Status of Gestational Sows in the Tropics - Ojo, O. A.; Awoniyi, D. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
A ten-week trial was conducted to evaluate the efficacy of orally administered tomato juice (ToJ) on the hematological and reproductive performance of gestational sows raised at Omolara Farms, Ogbagba town, Kwara State. Sixteen (n=16) gestational sows within 4th -6th weeks of gestation were randomly allotted into four treatment groups, having four replicates, with one sow representing a replicate. Treatment 1, the control received 60 mls of clean water, Treatment 2 received 1g of Vitamin C in 60 mls of water, Treatment 3 and Treatment 4 received ToJ at 60mls and 120 mls respectively. At 10th week of experiment, blood samples were collected via marginal ear vein, hematological parameters evaluated include packed cell volume (PCV), red blood cell (RBC), hemoglobin, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), white blood cell (WBC) and platelet. Repoductive data monitored include; number of piglets per sow (NPPS), mortality rate, number of stillbirth piglets (NSBP), number of surviving piglets (NSP), number of piglets at birth (NPB). Result revealed that hemoglobin and WBC values were significantly depressed, while being significamtly elevated in pregnant sows administered with 60mls and 120mls ToJ. NPPS, NPB, NSBP and mortality rate were significantly elevated at 60 mls ToJ, while the reduced values of these parameters were recorded at 120 mls ToJ, as compared to the values observed in sows given Vitamin C. Serum antioxidant enzymes were elevated at 120 ToJ. Therefore, its recommended that ToJ inclusion could enhance performance of pregnant sows at 120 mls under tropical condition